Diet influence on egg production of the copepod Acartia tonsa (Dana, 1896) - Priscila F. Teixeira; Sonia M. Kaminski; Tatiana R. Avila; Alessandro P. Cardozo; José G.F. Bersano; Adalto Bianchini (Anais da Academia Brasileira de Ciências, 2010)
Egg production in the copepod Acartia tonsa was evaluated using different densities of the microalgae Thalassiosira weissflogii, Chaetoceros muelleri and Isochrysis galbana. Male and female were kept under controlled conditions (salinity 30, 20°C, photoperiod 12L:12D), acclimated to the experimental conditions and left over a period of 24 h to allow copulation. Algal densities tested were equivalent in biovolume and corresponded to 0, 2.5, 5, 10, 20, 40 and 60.10³ cells.mL-1 of T weissflogii. Ten acclimated female were separated, transferred to glass bottles and exposed for further 24 h to the corresponding experimental medium. After this period, the eggs were fixed and counted. Copepod egg production reached a threshold value when T weissflogii, C. muelleri and I. galbana were supplied at 10.10³, 140.10³ and 640.10³ cells.mL-1, respectively. Mean egg production corresponded to 28.0 ± 0.5, 20.1 ± 1.0 and 22.0 ± 3.5 eggs.female-1 .day-1, respectively. Copepods fed T weissflogii showed the highest mean egg production while those fed I. galbana reached a maximum egg production when the algae were supplied at a density two- to fourfold higher, considering the biovolume of T weissflogii and C. muelleri. These differences are explained considering the different sizes of the microalgae used to feed the copepods. A produção de ovos do copépode Acartia tonsa foi avaliada utilizando diferentes densidades das microalgas Thalassiosira weissflogii, Chaetoceros muelleri e Isochrysis galbana. Machos e fêmeas foram colocados sob condições controladas (salinidade 30, 20°C, fotoperíodo 12L:12D), aclimatados às condições experimentais e mantidos juntos por 24 h para permitir a copula. As densidades de algas foram equivalentes em biovolume e corresponderam a 0, 2,5, 5, 10, 20, 40 e 60,10³ células.mL-1 de T. weissflogii. Dez fêmeas aclimatadas foram separadas, transferidas para frascos de vidro e expostas por mais 24 h ao meio experimental correspondente. Após este período, os ovos foram fixados e contados. A produção de ovos alcançou um valor limiar quando T. weissflogii, C. muelleri e I galbana foram oferecidas a concentrações de 10,10³,140,10³ e 640,10³ células.mL-1, respectivamente. A média de produção de ovos correspondeu a 28,0 ± 0,5, 20,1 ± 1,0 e 22,0 ± 3,5 ovos.fêmea-1.dia-1, respectivamente. Copépodes alimentados com T. weissflogii mostraram a maior produção de ovos média enquanto os alimentados com I. galbana alcançaram uma produção de ovo máxima quando as algas foram providas a uma densidade de duas a quatro vezes maior, considerando o biovolume de T. weissflogii e C. muelleri. Estas diferenças podem ser explicadas considerando os diferentes tamanhos das microalgas utilizadas para alimentar os copépodes.